Experimental and ab initio Investigation on the Effect of CO and CO2 during Hydrodeoxygenation of m‐Cresol over Co/SBA‐15. Issue 7 (8th March 2023) - Teles, Camila A.; Gueddida, Saber; Deplazes, Roger; Ciotonea, Carmen; Canilho, Nadia; Lebègue, Sébastien; Dhainaut, Jérémy; Badawi, Michael; Richard, Frédéric; Royer, Sébastien
Abstract: The hydrodeoxygenation (HDO) is a fundamental step in the production of biofuels from lignin, and the catalyst type and reaction conditions can play an important role. In this work, Co nanoparticles finely dispersed in the porosity of SBA‐15 stand out a high selectivity toward deoxygenated products (63 % of methylcyclohexenes and 16 % of methylcyclohexane) in the HDO of m‐cresol (30 bar of pressure, temperature of 350 °C). The effect of co‐feeding CO and CO2, which can be present in the pyrolysis gas after transformation of carboxylic acids, was investigated. An unexpected positive effect on the stability of the catalyst was observed when CO2 was added in the feed stream. On the contrary, the presence of CO led to a strong decrease of the m‐cresol conversion. These experimental findings are supported by DFT calculations which show that the m‐cresol is much more strongly adsorbed than CO2 at the Co@SiO2 interface while the interaction energy of CO is close to the one of m‐cresol. Abstract : Supported Nanocatalysts : Cobalt nanoparticles finely supported on SBA‐15 shows a high selectivity toward methylcyclohexenes in the HDO reaction of m‐cresol. The feed stream composition significantly affects the stability of catalyst. The presence of CO2 inhibits catalyst deactivation while CO accelerates deactivation due to its strong and irreversible adsorption on active sites.